Evaluation of the Current Opioid Misuse Measure among substance use disorder treatment patients - Ashrafioun, Lisham (J Subst Abuse Treat, 2015)
The Current Opioid Misuse Measure (COMM) has demonstrated promising psychometric properties among pain clinic and primary care patients. Given the high prevalence of the nonmedical use of prescription opioids among substance use disorder patients, the COMM may also be useful in substance use disorder treatment settings. The purpose of this study was to assess the factor structure and validity of the COMM in a sample of substance use disorder patients. Participants (n = 351) were recruited from a large residential substance use disorder treatment center and completed the COMM and several questionnaires assessing various substance use and health functioning characteristics. Factor analyses yield a two-factor solution; however, each of the items in the second factor cross-loaded onto the first factor and just one factor was retained. To provide support for this new 11-item COMM, we found that higher scores on this COMM were associated with greater drug use severity, greater endorsement of positive, negative, and pain relief outcome expectancies related to opioid use, increased pain intensity, and decreased physical and mental health functioning. These findings provide initial support for the psychometric properties of this version of the COMM adapted for substance use disorder treatment settings. Given its promising psychometric properties, the 11 items of the COMM to evaluate the nonmedical use of prescription opioids has potential utility among substance use disorder patients. The COMM could be used to examine nonmedical use over the course of treatment and to aid treatment planning. It could also be used in research as an outcome measure.